Overfertilization reduces tomato yield under long-term continuous cropping system via regulation of soil microbial community composition - Song, Qiaobo; Fu, Hongdan; Shi, Qingwen; Shan, Xuan; Wang, Zhen; Sun, Zhouping; Li, Tianlai (Frontiers in Microbiology, 2022)
Long-term monoculture cropping and overfertilization degrade soil fertility, which reduces crop growth and promotes the development of soil-borne diseases. However, it remains unclear what the temporal effects of the above factors are on the tomato yield and microbial community structure. Thus, a greenhouse experiment with different amounts of fertilization [2,196 kg ha−1 (control) and 6,588 kg ha−1 (overfertilization) of inorganic fertilizers (NPK)] was carried out with the soils used previously for 1, 2, and 12 years under monoculture of tomato. A 12-year overfertilization decreased soil pH by 1.37 units. Soil electrical conductivity (EC) and concentrations of soil nutrients are enhanced with the increase in tomato cropping duration. Higher content of soil nutrients was found under overfertilization compared to the control in the 12-year soil. Overfertilization decreased the activity of β-1,4-glucosidase (BG) and oxidase compared to the control in the 12-year soil. Bacterial diversity and richness decreased by 6 and 31%, respectively, under overfertilization in 12-year soil compared to the control. The relative abundance of Gemmatimonas and Gp6 in 12-year soil under overfertilization was 17 and 78%, respectively, lower than in control soil. Soil pH and total carbon (TC) were the major factors explaining changes in microbial composition. A 38% decrease in yield was caused by overfertilization in 12-year soil compared to the control. Microbial community composition was the main factor that moderated tomato yield. In addition, fertilization rather than cropping duration had a greater impact on tomato yield. Therefore, our results suggest that long-term overfertilization influenced soil pH, soil TC, and soil microbial community composition to regulate tomato yield.